Social identity and political polarization: Evidence on the impact of identity on partisan voting trade - Dominik Duell; Justin Mattias Valasek (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2017)
While scholars and pundits alike have been pointing to a trend of increasing partisan affect in the US, there has been very little analysis as to how partisan affect impacts the decisions of voters. We hypothesize that affective polarization may effect voting both through an expressive channel, as voters become more likely to vote instinctively, and through an instrumental channel, as voters expect candidates to take decisions that are more favorable towards their partisan in-group. To explore this hypothesis, we conduct a laboratory experiment designed to separate between the expressive and instrumental impact of affective polarization, and find evidence that affect significantly impacts subjects' voting decision through both channels. Importantly, however, we show that the instrumental impact of affective polarization depends on the underlying degree of polarization in policy preferences. Additionally, in contrast to the existing literature, our study demonstrates that affective polarization has a clear negative impact on social welfare by decreasing the likelihood that high valence candidates win elections. Lastly, we compare the impact of affect between groups that are formed using a neutral prime (minimal groups) and groups that are formed using the subjects' stated partisan identity. Surprisingly, we find no difference in voting behavior between the two treatments, implying that among a group of individuals that are otherwise relatively homogenous (university students) the impact of partisan identity is no greater than an arbitrary label.
Keywords: 330; political polarization; social identity; affective polarization